EFFECT OF THE CHEMICAL ADMIXTURE “SIKA 43-36” ON THE PROPERTIES OF PORTLAND CEMENT - Bazarbaev Makhsetbay Muratbayevich,; Shakirov Tuyg‘unjon Turg‘unovich, (TADQIQOTLAR, 2025)
Abstract: This paper presents the results of a study on the effect of the chemical admixture “Sika 43-36” on the physical and mechanical properties of portland cement CEM I 42.5N produced by “AKKERMAN CEMENT” which was used as a binder for lightweight concrete based on foamed glass aggregate. The influence of the admixture on water demand, workability, setting time, and strength characteristics of the cement was investigated.